The Tourism Awareness Group (Pokdarwis) Plays a Role in Managing the Panjaratan River Cruise in Panjaratan Village, Tanah Laut Regency, South Kalimantan. - Anisa, Siti Nor; Abbas, Ersis Warmansyah; Triyono, Sigit; Syarifuddin, Syarifuddin; Sari, Raihanah (Universitas Lambung Mangkurat, 2026)
The Tourism Awareness Group (Pokdarwis) is an organization involving the community that plays a role in managing tourism in a region. This research focuses on the role of the Tourism Awareness Group (Pokdarwis) in managing the Panjaratan River Cruise tour located in Tanah Laut Regency, South Kalimantan. This Panjaratan River Cruise tour faces challenges in terms of management carried out by Pokdarwis. The reason for conducting this research is because there has been no specific study of the role of Pokdarwis in managing the Panjaratan River Cruise tour. This tour is an ecotourism destination that has a rich ecosystem and endemic animals, especially the proboscis monkey (Nasalis larvatus), which is the main attraction of this area. Therefore, this study aims to describe the role of Pokdarwis in managing the Panjaratan River Cruise tour in Tanah Laut Regency. This research method uses a qualitative research method to describe the Tourism Awareness Group (Pokdarwis) Role in Managing Panjaratan River Tours in Panjaratan Village, Tanah Laut Regency, South Kalimantan . The subjects in this study were the local community in the tourist area, especially Pokdarwis members who manage the area, as well as visitors . Data collection techniques were carried out by observation, interviews, and documentation. Data analysis used data reduction based on research objectives, data presentation based on descriptions, and data conclusions based on drawing conclusions. Data validity testing was carried out using triangulation techniques. The results of the study showed that the Tourism Awareness Group (Pokdarwis) plays a role in the management of the Panjaratan River Cruise Tourism in Panjaratan Village, Tanah Laut Regency, South Kalimantan, which shows that Pokdarwis plays an active role in planning, implementing, promoting, and empowering local communities. The conclusion is that the Tourism Awareness Group (Pokdarwis) has a strategic role in the management of the Panjaratan River Cruise Tourism. Pokdarwis is able to improve the quality of management, community participation, and support the sustainability and development of local tourism potential in a sustainable manner